ENTRAVES DO DESENVOLVIMENTO REGIONAL E SOCIAL DO QUILOMBO SANTA ROSA DOS PRETOS E A LUTA PELA TITULAÇÃO DE TERRAS - OLIVEIRA, Andresa Venancia Lima de (2024)
This study examines the relevance of land titling for the socioeconomic development of the quilombola community Santa Rosa dos Pretos, located in the municipality of Itapecuru Mirim, Maranhão. The main objective was to analyze how the titling process contributes to the socioeconomic development of this community. It is identified as an essential element to guarantee the permanence of quilombolas in their territory and to strengthen social and cultural structures, playing a significant role in the regional development of the community. The study focuses on land as a vital space for the reproduction of community life and discusses title as a fundamental right for the preservation of ancestry. The research adopts a methodology based on historical-dialectical materialism, with a qualitative-quantitative approach. The methodological instruments included the application of questionnaires to the community and interviews with local leaders, in addition to the analysis of bibliographic, documentary and empirical sources. The analysis highlights the social, political and economic relationships that influence the regularization process. The results indicate that it has a direct impact on improving the quality of life and expanding the individual freedoms of community members, in line with Amartya Sen's development theory. The research reveals that land regularization contributes to strengthening cohesion social and for the preservation of cultural traditions, in addition to promoting a more favorable environment for local economic development. In this way, not only is land ownership assured, but it also constitutes a fundamental mechanism for socioeconomic development and the guarantee of the community's fundamental rights.